Comparing fourth-year medical students’ procedural surgical skill learning outcomes between third-person point-of-view video lectures and first-person point-of-view immersive virtual reality: a pilot study of surgically implanting a subdermal drain on cadavers - Neuwirth, Lorenz S.; Ng, Sam; Devors, Sandrine; Lonjon, Nicolas; Ros, Maxime (Frontiers in Virtual Reality, 2024)
The use of virtual reality (VR) training in medical school education has increased over the last decade partly due to coronavirus-19 (COVID-19) and due to technology advancements in this integrative area. As medical students are being trained in new pedagogical interventions, it is important to drill-down and focus on the areas of most translational concern for assessing their competency and proficiency. Thus, the present pilot study sought to evaluate a group of fourth-year medical students’ ability to learn a modified medical school curriculum on implementing a subdermal drain by first learning how to stitch on a silicone model (i.e., proper stitching only) and then being randomly assigned to either a third-person point-of-view (TP-POV) or first-person point-of-view (FP-POV) immersive VR group to learn how to conduct the surgical procedure (i.e., conceptually and procedurally). Then, the participants’ surgical procedural motor skills were assessed on a single attempt to demonstrate their competency and proficiency on a cadaver. The results showed that the pedagogical learning differences in FP-POV immersive VR improved the cleanliness and accuracy of the surgical dissection movement and drain placement with 100% proficiency in the first attempt at implementing this surgical technique on a cadaver. Additionally, there was statistically significant improvement in the dissection movement (p < 0.05*) and the tension test (p < 0.01**) in the FP-POV group compared to the TP-POV group, even with a small sample size in the present pilot study. These findings offer unique training opportunities to be considered when designing future VR curriculum with the suggested use of repeated-measures designs on the surgical procedural motor skills to assess learning curves and their potential translations in reducing operating room errors, costs, planning and scheduling times, and surgery overlaps, thereby positively contributing to a more efficient and safer OR surgical experience by staff and patients in the near future.